Attitude toward mathematics: teachers’ capacity to consider them - Legañoa Ferrá, Dra. C. María de los Ángeles; Báez Suero, M. Sc. Isidro; García Batán, Dr.C. Jorge (Transformación, 2024)
This article approaches the preparation of the teachers of the primary level to face the negative attitudes of the pupils towards mathematics, as a component of the affective domain. Prior studies in the area of affective domain of mathematics and his influence in pupils’learning were documented, as well as the role of the teachers to attend to consider affective problems associated to learning. Dominican Republic is one of the countries with the lowest scores in mathematics at the primary level in Latin America and the Caribbean. To find out whether the initial training of teachers at the primary level of the Dominican Republic is considering mathematics teacher education, with an emphasis in mathematics affective education, a diagnosis was made at "Salomé Ureña" College of Education of Santo Domingo. Several indicators and instruments were used for data collection. The main techniques used in the diagnosis were document reviewing, text commenting, written test, questionnaire, interviews and supervising teachers’ performance. The initial findingwascompared to the indicators to conclude thatteachers needs some training to solve the contradiction between the demands on teachers in the field of affective education mathematics and current college of education curriculum limitations.